Evaluación de la evolución del daño de formación en pozos representativos del Campo Castilla en el periodo de tiempo del año 2014 al año 2018 (2019)
The main objective of this work was to evaluate the evolution of the damage of the K1 Formation for Campo Castilla by studying five (5) representative wells according to the five (5) areas of the Field and comparing the results with the results of a previous study carried out in 2014 For the development of the work the Reveal Software was used, through which the approach of the behavior of the deposit was made, in addition to the impact of the production on its performance, with this information the proportion in which the different types of formation damage was determined They affected the productivity of the well. In addition, the nodal analysis was carried out by means of the Prosper Software, which allowed to determine the initial formation damage, the current formation damage, the pressure drop due to the presence of damage and to establish the IPR curves for each well simulating the incremental of production with damage removal. The determination of the main type of training damage is the basis for the damage removal processes, since, for the work to be effective and efficient, the damage that occurs in greater proportion must be attacked. The simulation of the damage removal allowed to establish an economic benefit once said activity was carried out.